To explore the impact of the ERP on the performance of the accounting processes of Kazi and Kazi tea estate - Touhid, M M Shadman (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023